Application of Rose Bengal Test and ELISA in Meat Juice for Monitoring of Brucellosis among Cattle Carcasses at Erbil City, Iraq - Dhary Alewy AL MASHHADANY (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies, 2019)
Brucellosis is a global zoonotic bacterial disease. It is also an ever-increasing public health concern, particularly in endemic regions such as Kurdistan region in Middle East. Samples of meat juice were screened for anti-Brucella antibodies via Rose Bengal Test (RBT) and ELISA from January to June 2018. Bacteriological isolation of Brucella sp. from meat samples was also performed. The overall prevalence of bovine brucellosis is 7.7%, 6.6%, and 4.9% by RBT, ELISA, and culture-based test respectively. Based on sensitivity and specificity, ELISA outperforms RBT in comparison to culture results as the gold standard test. Nonetheless, both tests showed good efficiency in comparison to culture approach. In terms of temporal changes of brucellosis rate, spring progress is strongly associated (r²=0.96) with increase in seroprevalence. In conclusion, the prevalence of bovine brucellosis in Erbil city is alarming. Countermeasures should be taken to mitigate the economic losses and transmission to human.